Protection of Socio-Economic Rights by the Constitutional Court of the Russian Federation - Svetlana Karamysheva (The Constitutional Court of the Republic of Indonesia, 2020)
The article studies practice of the Constitutional Court of the Russian Federation in the field of socio-economic rights. The statistical data analysed illustrates the ever-present socio-economic theme among constitutional complaints lodged with the Constitutional Court, with the lowering of overall proportion of such complaints and increasing of the number of such complaints related to defence of property. Such statistics appear to be consistent with the Court’s role in the ongoing transition from Soviet-style planned economy to free market, which implies a substantial shift of obligations connected with property management and social responsibilities from the State to citizens themselves. It follows from the Constitutional Court practice and doctrine that such shift should be done delicately, giving the citizens sufficient period of time to adapt to the changes. In the article, the author focuses on the following categories of complaints considered by the Constitutional Court of the Russian Federation: protection of the right to private property and protection of the right to pension provision. The author observes that the delicate balance that needs to be preserved when dealing with the cases of this type and the slow-pace nature of the transition process often results in criticism towards the Court, notwithstanding the rationale of its decisions. It follows that such criticism is somewhat natural; what matters is the Court’s understanding of its mission in the socio-economic field, and maintaining balanced and well-reasoned approach in development of its case-law.